Mineralization Content Alters Osteogenic Responses of Bone Marrow Stromal Cells on Hydroxyapatite/Polycaprolactone Composite Nanofiber Scaffolds - Ketul C. Popat; Timothy T. Ruckh; Justin R. Weaver; Derek A. Carroll (Journal of Functional Biomaterials, 2012)
Synthetic tissue scaffolds have a high potential impact for patients experiencing osteogenesis imperfecta. Using electrospinning, tissue scaffolds composed of hydroxyapatite/polycaprolactone (HAp/PCL) composite nanofibers were fabricated with two different HAp concentrations—1% and 10% of the solid scaffold weight. After physico-chemical scaffold characterization, rat bone marrow stromal cells were cultured on the composite scaffolds in maintenance medium and then in osteogenic medium. Quantitative PCR, colorimetric assays, immunofluorescent labeling, and electron microscopy measured osteogenic cell responses to the HAp/PCL scaffolds. In maintenance conditions, both Hap/PCL scaffolds and control scaffolds supported cell colonization through seven days with minor differences. In osteogenic conditions, the 10% HAp scaffolds exhibited significantly increased ALP assay levels at week 3, consistent with previous reports. However, qPCR analysis demonstrated an overall decrease in bone matrix-associated genes on Hap/PCL scaffolds. Osteopontin and osteocalcin immunofluorescent microscopy revealed a trend that both mineralized scaffolds had greater amounts of both proteins, though qPCR results indicated the opposite trend for osteopontin. Additionally, type I collagen expression decreased on HAp scaffolds. These results indicate that cells are sensitive to minor changes in mineral content within nanofibers, even at just 1% w/w, and elucidating the sensing mechanism may lead to optimized osteogenic scaffold designs.